2021
DOI: 10.3390/ma14040704
|View full text |Cite
|
Sign up to set email alerts
|

Compaction of Cohesive Granular Material: Application to Carbon Paste

Abstract: Carbon-like materials such as the anode and the ramming paste play a crucial role in the efficiency of the Hall–Héroult process. The mechanical behavior of these materials during forming processes is complex and still ill-understood. This work aimed to investigate experimentally the mechanical behavior of a carbon paste used in the aluminum industry under different loading conditions. For this purpose, experiments consisting of (1) relaxation tests at different compaction levels, (2) quasi-static cyclic tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…The aggregates’ breakage during this experiment was captured by an acoustic waves detection system and was highlighted by a softening behavior on the stress–strain curves [ 21 ]. A study that investigated the behavior of the carbon paste subjected to cyclic loadings was [ 22 ]. Quasi-static cyclic tests at different strain amplitudes were carried out on a room-temperature ramming paste.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The aggregates’ breakage during this experiment was captured by an acoustic waves detection system and was highlighted by a softening behavior on the stress–strain curves [ 21 ]. A study that investigated the behavior of the carbon paste subjected to cyclic loadings was [ 22 ]. Quasi-static cyclic tests at different strain amplitudes were carried out on a room-temperature ramming paste.…”
Section: Introductionmentioning
confidence: 99%
“…Quasi-static cyclic tests at different strain amplitudes were carried out on a room-temperature ramming paste. It was shown that decreasing the strain amplitude applied to the carbon paste would lead to a considerable decrease in the axial stress and to an increase in the number of cycles needed to reach the target density [ 22 ]. The authors presented the following hypothesis: lower strain amplitudes during cyclic loadings enhance the aggregates rearrangement and the relaxation of pore pressure during the unloading phases.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations